An Integrative Analysis of the Putative Gefitinib-resistance Related Genes in a Lung Cancer Cell Line Model System - Han, Xiaohong; Liu, Manjiao; Wang, Shuai; Lv, Guanting; Ma, Li; Zeng, Changqing; Shi, Yuankai (Current Cancer Drug Targets, 2015)
The epidermal growth factor receptor-tyrosine kinase inhibitors (EGFRTKI), such as gefitinib and erlotinib have improved the survival of patients with nonsmall cell lung cancer (NSCLC). Unfortunately, acquired resistance will eventually develop in most patients who initially respond to the therapy. Currently known molecular mechanisms for such an acquired resistance may interpret only about 70% of clinical cases. In this study, using NSCLC cell model H1650, we constructed a gefitinib resistant cell line H1650GR through long term drug exposure with increased doses. RNA sequencing and whole genome SNP array were applied to investigate the transcriptome and genome alterations possibly involved in gefitinib resistance. By comparing the expression profiles between H1650GR and H1650 cells, we identified a large set of differentially expressed genes (DEGs), including FOXM1. In the PI3K/AKT pathway, AKT activity was predicted to be inhibited. However, genes that play important roles in gefitinib-induced apoptosis, including TP53, FOXO3 and BAD, were not up-regulated. Ingenuity Pathway Analysis (IPA) canonical pathway analysis showed that p53 signaling was inhibited in H1650GR cells, with down-regulation of pro-apoptosis genes FAS, PUMA, NOXA, and upregulation of anti-apoptosis genes BIRC5/Survivin. Besides, a large number of immune response-related genes were differently expressed, the role of which in gefitinib resistance requires further investigation. Whole genome copy number alterations (CNAs) were also analyzed and NOXA was located in the H1650GR unique copy number loss region, 18q21. Our results suggested that the much higher EGFR-TKI resistance in H1650GR may be produced by the integration of multi-aspect factors.
Keywords: drug resistance